Link between culture(s) and economics: conciliatory approach (Economic and Political Thought, 2018)
The author of the article supports the thesis that culture and culturalfactors should be incorporated into the theory of economics. It is often postulatedthat this theory reflects reality better and thus one solution is proposedin the article. Attention is drawn to the fact that the notion of culture isinaccurate and many definitions exist. Methodological problems may be onereason for the lack of interest of economists in this topic. The author acceptsthe definition associated with values and thus eliminates a narrow understandingof culture through the prism of art and creative industries.It is demonstrated in the article that even though the issue is relativelynew, there are historical grounds for it. The connection between cultures andeconomics as well as methodological remarks on further research are shown.The author tries to omit problems that have already been discussed in therelatively scarce literature.
Keywords: methodology, culture, economic theory, economics